Exploratory study on the effects of country-of-origin and brand name in Singapore. - Chiam, Pey Feng. (2008)
This study aims to find out how country-of-origin and brand name affects consumer product evaluations through factors such as country bias etc. Beer is used as the medium for testing our hypothesis.